Dampak Pandemi COVID-19 Terhadap Pola Makan dan Aktivitas Fisik Pada Remaja Obese dan Overweight Berdasarkan Persen Lemak Tubuh - Fatma Syukrina; Ratu Ayu Dewi Sartika; Rizti Millva Putri (LPPM Hang Tuah Pekanbaru, 2023)
Background: Obese and overweight adolescents have a high risk of COVID-19 susceptibility and severity compared to normal nutritional status. Although a healthy dietary pattern and physical activity do not entirely prevent infection, they play a substantial role in the host's response to infectious agents. The purpose of this study is to analyze the changes in dietary patterns and physical activity during the COVID-19 pandemic in overweight and obese adolescents based on body fat percentages (BFP). Method: A cross-sectional study using purposive sampling was conducted on 159 adolescents from selected high schools in West Lampung, Indonesia. Data collection was assessed using a body composition scale and Food Frequency Questionnaire (FFQ). Data analysis was performed using SPSS. The Wilcoxon signed-rank test was used to analyze the differences between the two adolescent groups. Result: The overweight and obese adolescents group increased the consumption of unhealthy foods and beverages compared to the normal group (p<0.05). Both groups significantly increased the fruit rich in vitamin C consumption (p<0.05), but no significant difference in vegetable consumption (p>0.05). Both groups were found to have no significant difference in physical activity, both before and during the COVID-19 pandemic (p>0.05). Conclusion: Adolescents with normal body fat percentages (BFP) tend to have better dietary patterns, in contrast to overweight and obese adolescents with a high BFP who tend to have a decrease in the quality of their dietary patterns. Then, both groups were found to have a significant decrease in the frequency of physical activity during the COVID-19 pandemic.